Variations in Antimicrobial Activities of Human Monocyte-Derived Macrophage and Their Associations With Tuberculosis Clinical Manifestations - Tram, Trinh T. B.; Ha, Vu T. N.; Thu, Do D. A.; Dinh, Tran D.; Nhung, Hoang N.; Hanh, Nguyen T.; Phu, Nguyen H.; Thwaites, Guy E.; Thuong, Nguyen T. T. (Frontiers in Cellular and Infection Microbiology, 2020)
Macrophages play a significant role in preventing infection through antimicrobial activities, particularly acidification, and proteolysis. Mycobacterium tuberculosis (Mtb) infection can lead to diverse outcomes, from latent asymptomatic infection to active disease involving multiple organs. Monocyte-derived macrophage is one of the main cell types accumulating in lungs following Mtb infection. The variation of intracellular activities of monocyte-derived macrophages in humans and the influence of these activities on the tuberculosis (TB) spectrum are not well understood. By exploiting ligand-specific bead-based assays, we investigated macrophage antimicrobial activities real-time in healthy volunteers (n = 53) with 35 cases of latent TB (LTB), and those with active TB (ATB), and either pulmonary TB (PTB, n = 70) or TB meningitis (TBM, n = 77). We found wide person-to-person variations in acidification and proteolytic activities in response to both non-immunogenic IgG and pathogenic ligands comprising trehalose 6,6'−dimycolate (TDM) from Mtb or β-glucan from Saccharamyces cerevisiase. The variation in the macrophage activities remained similar regardless of stimuli; however, IgG induced stronger acidification activity than immunogenic ligands TDM (P = 10−5, 3 × 10−5 and 0.01 at 30, 60, and 90 min) and β-glucan (P = 10−4, 3 × 10−4 and 0.04 at 30, 60, and 90 min). Variation in proteolysis activity was slightly higher in LTB than in ATB (CV = 40% in LTB vs. 29% in ATB, P = 0.03). There was no difference in measured antimicrobial activities in response to TDM and bacterial killing in macrophages from LTB and ATB, or from PTB and TBM. Our results indicate that antimicrobial activities of monocyte-derived macrophages vary among individuals and show immunological dependence, but suggest these activities cannot be solely responsible for the control of bacterial replication or dissemination in TB.